Fourth order random differential equation / D.S. Palimkar and P.R. Shinde - Palimkar, D. S.; Shinde, P.R (2015)
In this paper, an existence of random solution is proved for a periodic boundary value problem of fourth order random differential equation through an algebraic random fixed point theorem of Dhage.